Effect of Calcitriol Treated Mesenchymal Stem Cells as an Immunomodulation Micro-environment on Allergic Asthma in a Mouse Model - Ghalavand, Majdedin; Gouvarchin Ghaleh, Hadi Esmaeili; Khafaei, Mostafa; Paryan, Mahdi; Kondori, Bahman J.; Nodoushan, Majid Mirzaei; Vazifedust, Soheil; Mohammadi-Yeganeh, Samira (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Allergic asthma is a chronic inflammatory illness of the respiratory system characterized by an increase in the number of inflammatory cells in the airways and trouble breathing. Mesenchymal stem cells (MSCs) have the potential to be used in inflammatory diseases as a cellular immunosuppressive treatment. They express calcitriol receptors and communicate with other immunocytes, which increases their anti-inflammatory activity. This study aimed to determine the effects of calcitriol-treated MSC treatment on allergic asthma pathways in a mouse model. Methods: To generate a mouse model of asthma, the mice were sensitized intraperitoneally with ovalbumin (OVA) and aluminum hydroxide emulsion and then challenged intra-nasally with OVA. On day 14, experimental mice received tail vein injections of calcitriol-treated MSCs in PBS prior to allergen exposure. The cytokines assays including IL-4, 10, 12, 17, TGF-β and IFN-γ, splenocytes proliferation, and histological examination of lungs samples were performed. The mice were sensitized with OVA and the response to dexamethasone treatment was compared. Results: Calcitriol-treated MSCs significantly increased the levels of IL-12, TGF-β, and IFN-γ compared to non-treated MSCs groups. Moreover, calcitriol-treated and non-treated MSCs significantly decreased IL-4 and IL-17 compared to asthmatic groups. The results of the histopathological examination showed that calcitriol-treated MSCs reduced the accumulation of inflammatory cells and bronchial wall thickening in comparison with the asthma group. Conclusion: Using the allergic asthma model, we were able to show that calcitriol-treated MSCs had an inhibitory impact on airway inflammation. Our findings suggest that the injection of calcitrioltreated MSCs may be a viable treatment option for allergic asthma.
Keywords: calcitriol